How do autistic severity and family functioning influence parental stress in caregivers of children with autism spectrum disorder in China? The important role of parental self-efficacy - Kishimoto, Tomoko; Liu, Shuang; Zhang, Lumei; Li, Shaowei (Frontiers in Psychology, 2023)
Introduction Parental stress among primary caregivers of children with autism spectrum disorder (ASD) is a significant concern. While previous research indicates that both family and child factors substantially influence parental stress, a few studies have comprehensively examined these factors from family, parent, and child perspectives. Moreover, the psychological mechanisms underlying parental stress remain underexplored. Method This study obtained a valid sample of 478 primary caregivers of children diagnosed with ASD in China and employed mediation and moderated mediation analyses to investigate the relationships between family adaptability and cohesion (FAC), ASD severity, parental self-efficacy, and parental stress. Result Results revealed that higher FAC was linked to reduced parental stress through increased parental self-efficacy. The indirect effect of parental self-efficacy was more substantial for caregivers of children with severe symptoms than those with mild symptoms. Discussion These findings offer insights into how FAC influences parental stress and underscore the importance of parental self-efficacy as a coping resource for mitigating parental stress. This study provides valuable theoretical and practical implications for understanding and addressing parental stress, particularly in families raising children with ASD.